Exploring patient–provider decision-making for use of anticoagulation for stroke prevention in atrial fibrillation: Results of the INFORM-AF study. (1st April 2019) - Pokorney, Sean D; Bloom, Diane; Granger, Christopher B; Thomas, Kevin L; Al-Khatib, Sana M; Roettig, Mayme L; Anderson, John; Heflin, Mitchell T; Granger, Bradi B
Abstract: Background: Atrial fibrillation is associated with stroke, yet approximately 50% of patients are not treated with guideline-directed oral anticoagulants (OACs). Aims: Given that the etiology of this gap in care is not well understood, we explored decision-making by patients and physicians regarding OAC use for stroke prevention in atrial fibrillation. Methods and results: We conducted a descriptive qualitative study among providers ( N =28) and their patients with atrial fibrillation for whom OACs were indicated ( N =25). We used purposive sampling across three outpatient settings in which atrial fibrillation patients are commonly managed: primary care ( n =14), geriatrics ( n =10), and cardiology ( n =4). Eligible patients were stratified by those prescribed OAC ( n =13) and not prescribed OAC ( n =12). Semi-structured, in-depth interviews assessed decision-making regarding risk and OAC use. Classical content analysis was used to code narratives and identify themes. Results among patients consisted of the overarching theme of trust in provider recommendations. Sub-themes included: awareness of increased risk of stroke with atrial fibrillation; willingness to accept medications recommended by their physician; and low demand for explanatory decision aids. Among physicians, the overarching theme was decisional conflict regarding the balance between stroke and bleeding risk, and the optimal medication to prescribe. Subthemes included: absence of decision aids for communication; and misperceptions around the assessment and management of stroke risk with atrial fibrillation. Conclusions: Patient involvement in decision-making around OAC use did not occur in this study of patients with atrial fibrillation. Improved access to decision aids may increase patient engagement in the decision-making process of OAC use for stroke prevention.